The physics of Duns Scotus : the scientific context of a theological vision - Cross, Richard, 1964- (Oxford : Clarendon Press ; New York : Oxford University Press, 1998)
This text contains detailed discussion and analysis of Dun Scotus's accounts of the nature of matter and the structure of material substance. His views on these matters are sophisticated and highly original.
1. Introduction: Physics and Duns Scotus -- 2. Prime Matter -- 3. Substantial Form -- 4. The Plurality of Forms -- 5. Composite Substance -- 6. Accidents and Accidental Unity -- 7. Quantity and Continuity -- 8. The Metaphysics of Continuity -- 9. Quantity: Change and Mass -- 10. Quality: Unity, Degree, and Change -- 11. Place and Space -- 12. Motion, Time, and Continuity -- 13. The Reality of Time -- App. The Metaphysics of Generation and Corruption.
Includes bibliographical references (pages 265-277) and indexes.
Keywords: Duns Scotus, John, -- approximately 1266-1308.; Philosophy of nature -- History; Physics -- Philosophy -- History